Iqbal’s ideas on science and the Muslims - Abdul Razak, Mohd Abbas (Kulliyyah of Science, IIUM, 2011)
Early Muslims were able to embellish their civilization with great achievements in the areas of science and technology. The Holy Qur’an not only speaks about spirituality but also on science and the natural world. The Qur’an was the driving force in encouraging the Muslim scholars to go into science and research. The zeal to understand the hidden message of Allah, in the natural world, made them learn from contributions made by earlier civilizations. In taking knowledge from others, early Muslims used the methodology of adopt, adapt and integrate. During their heydays, Muslim scholars were pioneers in many areas of knowledge and sciences; natural and social. The peak of Islamic civilization drew Europeans scholars to their centers of learning. In modern times, the European renaissance movement which started in the 14th century got the impetus from the culture of learning, doing research and exploration that was shown by the Muslim scholars of the Golden Age of Islam (750-1258). The decline of the Islamic empires and the internal conflicts within the Ummah in some ways made the Muslims to lag behind others in science and technology. This paper intends to explore the ideas of Iqbal (1873-1938) on science and what are the obstacles highlighted by him that hindered the Muslims’ march towards making this world a better place for them and others as well.